Pericardial Effusion Secondary to Amoebic Liver Abscess: A Rare Complication - Raza, Mohammad (Cureus, 2020)
Amoebiasis is a common infection widely prevalent in tropical countries with low income and poor sanitation. The clinical picture is usually nonspecific; however, invasion of the liver by Entamoeba histolytica could lead to an amoebic liver abscess (ALA). It is relatively uncommon in women and children. Though rare, extension of ALA into the lungs, pleural cavity, and pericardium may prove fatal. Pericardial amoebiasis is a rare complication which, if not treated early, could result in cardiac tamponade and subsequent death. The standard management option is eradication with metronidazole along with the drainage of fluid from the liver abscess and pericardial effusion. Herein, we present a case of a seven-year-old male child with ALA, who developed signs and symptoms suggesting pericardial effusion within a few days of hospital admission. Early diagnosis of pericardial complication and successful management of abscess resolved the pericardial effusion.